Fluoride removal from water using process residues from the cement, aggregate, and ceramic industries - Pont, Silvio Cesar Dal (2024)
Fil: Dal Pont, Silvio Cesar. Universidade do Extremo Sul Catarinense. Laboratório de Reatores e Processos Industriais; Brasil.